The Problems of Matching Objectives, Instruments, and Financial Flows in Regional Policy - N. E. Barbashova; Yu. V. Gerasimova (Мир новой экономики, 2019)
In the article, authors considered the relationship between the priorities of the regional policy of theRussian Federation, the applied instruments, and the corresponding financial ﬂows. The study was conducted on the basis of the analysis of normative legal acts of the Russian Federation in the field of regional policy, budget policy and strategic planning, as well as strategic and program documents of the Federal level. The authors paid special attention to the instruments of stimulation of regional economic development. The authors came to the conclusion that the successful implementation of regional policy is hampered by the problems associated with the incompleteness and inconsistency of the system of strategic planning documents, the lack of interdepartmental coordination, the redundancy of the number of incentive mechanisms, the complexity of managing financial ﬂows from various sources, and the gaps in information support. The findings of the study were tested on the example of the Primorsky Krai. According to the analysis, the authors have formulated recommendations for public authorities aimed at improving the effectiveness of incentive mechanisms of state regional policy.